BMC Oral Health - Goodridge, Alex.; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
BMC Oral Health is an open access, peer-reviewed journal that considers articles on all aspects of the prevention, diagnosis and management of disorders of the mouth, teeth and gums, as well as related molecular genetics, pathophysiology, and epidemiology. The journal welcomes submissions covering the following broad areas of research: Digital Dentistry Clinical Oral Healthcare Dental techniques: tools, materials and surgical research Epidemiology of oral health Oral Microbiology Delivery, management and promotion of oral health and dental care As a BMC Series journal, BMC Oral Health does not make editorial decisions based on the perceived interest or potential impact of a study. Manuscripts are considered for publication if they are scientifically valid. For research articles, this includes having a clearly defined and sound research question, appropriate methodology and analysis, and adherence to community-agreed standards relevant to the field.
Keywords: Dentistry; Mouth$1 (BSurgery.s; Dentistry; Oral and Maxillofacial Surgery